Factors Influencing Economic Growth in OIC Countries: A Panel Data Approach - Syaifullah; Heriangrum, Sri; Damirah; Lestari, Nurrizka Puji; Hudaifah, Ahmad (Universitas Airlangga, 2024)
Economic growth plays a crucial role in determining the success of a country's development, with each nation setting stable economic growth targets within its development agenda. The process of economic growth is influenced by various factors that can either drive or hinder the pace of growth. This study aims to analyze the impact of zakah growth, the scientific and technical journal articles, population, and unemployment rates on the economic growth of 10 member countries of the Organization of Islamic Cooperation (OIC) for the period 2002-2022 using a quantitative approach with a random effects panel data regression analysis technique and EViews 12 application for data management. As per the research findings, the variables of zakah and scientific and technical journal articles have a positive and significant relationship with economic growth. The population and unemployment rate have a negative and significant. Therefore, it is recommended that governments should improve efficiency in the management of zakah, allocate more budget for education and research, and formulate policies to promote innovation and collaboration between related sectors. It assists in achieving more awareness of zakah and participation in monitoring the utilization of zakah funds for society. The studies would help to see what variables affect economic growth.